2011
DOI: 10.1186/1758-2652-14-44
|View full text |Cite
|
Sign up to set email alerts
|

HIV and concurrent sexual partnerships: modelling the role of coital dilution

Abstract: BackgroundThe concurrency hypothesis asserts that high prevalence of overlapping sexual partnerships explains extraordinarily high HIV levels in sub-Saharan Africa. Earlier simulation models show that the network effect of concurrency can increase HIV incidence, but those models do not account for the coital dilution effect (non-primary partnerships have lower coital frequency than primary partnerships).MethodsWe modify the model of Eaton et al (AIDS and Behavior, September 2010) to incorporate coital dilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…More precisely, we multiply the monthly transmission probability by 0.8 if the index person has two partners, and by 0.6 if he or she has three partners. These assumptions imply that more concurrency is associated with a larger number of coital acts in the simulated population, and differ from another coital dilution modeling study that rests on the stronger assumption that higher levels of concurrency lead to a reduction in the population-level number of coital acts (Sawers, Isaac, and Stillwaggon 2011).…”
Section: Figurementioning
confidence: 86%
“…More precisely, we multiply the monthly transmission probability by 0.8 if the index person has two partners, and by 0.6 if he or she has three partners. These assumptions imply that more concurrency is associated with a larger number of coital acts in the simulated population, and differ from another coital dilution modeling study that rests on the stronger assumption that higher levels of concurrency lead to a reduction in the population-level number of coital acts (Sawers, Isaac, and Stillwaggon 2011).…”
Section: Figurementioning
confidence: 86%
“…In other words, if a person has 10 times as many simultaneously sexual partners, conventional model approaches may implicitly assume that each person has 10 times as many sexual encounters in a particular time period. However, data suggest that people with many simultaneous partners do not have a proportionate increase in frequency of sexual encounters per unit time, and therefore this implicit assumption may exaggerate the impact of concurrency on transmission risk [30]. …”
Section: Methodsmentioning
confidence: 99%
“…Coital dilution is the reduction in the number of sexual acts per partner when an additional, concurrent partner is added [1]. Concurrency is defined as having two or more sexual partnerships overlapping in time [2].…”
Section: Introductionmentioning
confidence: 99%
“…A common assumption in mathematical models is to preserve the number of acts per partnership under concurrency [3], but that implies the number of potential transmission events increases linearly with degree (the number of ongoing partners at any time). One model testing this assumption suggested that relatively modest levels of dilution (25% or higher) could erase the effects of concurrency [1], though the assumptions of this model also led to decreasing rates of activity over time.…”
Section: Introductionmentioning
confidence: 99%